Historical High Complexity Neurosurgery Development of One of the Poorest Brazilian Regions - Ramos, Silvio Pereira, Junior; Godoi, Bruno Bastos; Cordeiro, Patrício Jesus; Neto, Jorge Diniz; Gusmão, Sebastião Nataniel Silva (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Human development rates in the Vale do Jequitinhonha, state of Minas Gerais, Brazil, called “Misery Valley,” are among the lowest in the country, not to mention the often precarious psychosocial realities that daily contact with these families reveals. The history of neurosurgery at the Neurosurgical Reference Center at the Vale do Jequitinhonha e Mucuri dates from 2004, when the first neurosurgical procedures were performed in the recently organized Section of Neurosurgery. The historical surgical series shows the positive impact of the service. In 2007, the average was 3 neurosurgeries/month. In the last year, 2018, service growth boosted the record to 34.83 neurosurgeries/month. In addition to performing elective surgery, the neurosurgery team supports the emergency team by performing some neurosurgical procedures. The service number of patients operated since the development of the service is nearly 3,000. Neurosurgery at the Santa Casa de Caridade from Diamantina has been made comparable to the best national neurosurgery services.
Keywords: history; faculty; medical schools; neurosurgery